Responsible Innovation Framework for Interdisciplinary Precision Agriculture Research - Damilola Tobiloba Adereti; Omodolapo Eunice Ogunsola; Adekunle S. Toromade (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Precision agriculture represents one of the most significant technological transformations in modern farming, promising higher productivity, resource efficiency, and environmental sustainability. Yet, the rapid advancement of digital tools, artificial intelligence, remote sensing, and biotechnology raises profound ethical, social, and governance questions. This paper introduces a Responsible Innovation Framework for guiding interdisciplinary precision agriculture research, ensuring that technological advancements align with societal values, farmer needs, and sustainability goals. The framework emphasizes four interrelated dimensions: anticipation, reflexivity, inclusion, and responsiveness. Anticipation highlights the need to assess potential future impacts, risks, and unintended consequences of precision technologies. Reflexivity calls for researchers and innovators to critically examine their assumptions, objectives, and responsibilities within agricultural systems. Inclusion ensures that diverse voices including smallholder farmers, rural communities, policymakers, and industry stakeholders are actively engaged in research design and decision-making processes. Responsiveness stresses the capacity of innovation systems to adapt policies, practices, and technologies in light of new knowledge or shifting societal priorities. Methodologically, the framework integrates interdisciplinary perspectives, drawing from engineering, environmental science, economics, social sciences, and ethics to create a holistic approach to innovation. Case illustrations demonstrate how responsible innovation principles can be embedded in research projects, from drone-based monitoring systems to AI-driven decision support tools, ensuring that technological solutions are both scientifically robust and socially legitimate. Importantly, the framework bridges disciplinary silos, enabling collaborative problem-solving and promoting trust among stakeholders. By institutionalizing responsibility within precision agriculture research, the framework provides a roadmap for achieving not only technical excellence but also equitable and sustainable agricultural transformation. The study concludes that embedding responsible innovation into interdisciplinary research is essential for addressing global challenges of food security, climate resilience, and inclusive rural development.